Association between insecticide exposomics and cognitive function in older adults: an observational study based on NHANES 2011–2014 - Mengfan Zhang; Xiaofang Guo; Yuanjun Chen; Xinghua Liu; Xingdong Lin (Frontiers in Public Health, 2025)
ObjectiveThis study aims to investigate the association between exposure to insecticide exposomics and cognitive function, among adults aged 60 and above.MethodsWe employed a multi-stage probability sampling method to analyze data derived from the National Health and Nutrition Examination Survey (NHANES) conducted between 2011 and 2014. The study investigated the impact of insecticides exposure on cognitive performance, as measured by the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) Word Learning Test (CERAD-WL), CERAD Delayed Recall Test (CERAD-DR), Animal Fluency Test (ATF), and Digit Symbol Substitution Test (DSST). Logistic regression models were used to evaluate the impact, with adjustments for sociodemographic and lifestyle variables, and subgroup analyses were conducted to further elucidate the findings.ResultsA total of 1,544 participants were included after applying strict exclusion criteria. Logistic regression analysis disclosed a significant association between insecticides exposure and the risk of cognitive impairment. Specifically, for CERAD-WL, the unadjusted model showed an Odds Ratio (OR) of 0.68 (95% CI: 0.49–0.93), p = 0.0174, and the adjusted model showed an OR of 0.71 (95% CI: 0.51–0.99), p = 0.0466. CERAD-DR demonstrated an unadjusted OR of 0.64 (95% CI: 0.46–0.88), p = 0.0060, and an adjusted OR of 0.67 (95% CI: 0.47–0.94), p = 0.021. The DSST indicated a correlation with pesticide exposure in the unadjusted model with p = 0.0214. Herbicides were notably associated with ATF in the unadjusted model with an OR of 1.70 (95% CI: 1.14–2.53), p = 0.0093. However, after adjusting for sociodemographic and lifestyle variables, some associations were no longer statistically significant. For instance, the association between insecticides exposure and CERAD-WL performance became non-significant (OR: 0.80, 95% CI: 0.56–1.15, p = 0.2284), and similarly for CERAD-DR (OR: 0.72, 95% CI: 0.50–1.03, p = 0.0734).ConclusionOur study indicates an association between insecticides exposure and cognitive impairment, particularly affecting memory and delayed recall. Yet, the cross-sectional design prevents conclusive causality claims. Future research should adopt longitudinal approaches, utilize biological markers for precise exposure measurement, and apply advanced statistical techniques to better understand the exposure-outcome relationship. Including a broader age range and detailed confounder data will also strengthen causal inferences. While our findings offer preliminary evidence, more robust studies are necessary to confirm causality and guide preventive measures.